Effect of continuous jejunal perfusion of elemental and complex nutritional solutions on pancreatic enzyme secretion in human subjects. Issue 3 (March 1978) - Vison, N; Hecketsweiler, P; Butel, J; Bernier, J J
Abstract : Pancreatic secretion of lipase and chymotrypsin in response to elemental diets and a crushed food homogenate was studied in normal subjects. The solutions were infused at constant flow rates at the ligament of Treitz with polyethylene glycol as a nonabsorbable marker. A triple lumen tube was used, enabling collection of secretions at 35 and 70 cm from the infusion point. The results show that a crushed food homogenate has a greater stimulative effect on pancreatic enzyme secretion than the elemental solutions and that this can be directly related to its greater nitrogen content. The osmolality of the infused solutions does not appear to be important. The relative merits of the solutions tested and total parental nutrition in reducing pancreatic enzyme secretion are discussed.